2019
DOI: 10.1002/ca.23382
|View full text |Cite
|
Sign up to set email alerts
|

Do variants of the intercondylar notch predispose children to the injury of the anterior cruciate ligament?

Abstract: Differences in knee development result in morphological variations observed among individuals. Some of them predispose to significant knee injuries. Although the anatomical risk factors are well established in adults, there is still a need for further research in this area in the group of children. This work aims to determine the morphological variations of the intercondylar notch of the femur predisposing to anterior cruciate ligament (ACL) injuries in the pediatric population. Magnetic resonance imaging (MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
(23 reference statements)
0
14
1
Order By: Relevance
“…Although limited, there are publications in the literature revealing that the eminence structure is a risk factor for both ACL ruptures and avulsions of the tibial eminence. 23,25 In the present study, no relationship was found between the parameters defined and ACL rupture.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Although limited, there are publications in the literature revealing that the eminence structure is a risk factor for both ACL ruptures and avulsions of the tibial eminence. 23,25 In the present study, no relationship was found between the parameters defined and ACL rupture.…”
Section: Discussioncontrasting
confidence: 73%
“…Eminence height was calculated as the perpendicular distance between the line connecting the lowest parts of the articular surface of both tibial condyles and the highest point of eminentia. 23 Medial, lateral, and overall eminence height were recorded separately. Based on the line connecting the medial plateau and lateral plateau joint lines (the line connecting the lowest parts of the articular surface of both tibial condyles), the tibial plateau surface was determined on the coronal MRI, and the distance between the highest points of the medial and lateral eminence was calculated in the same plane.…”
Section: Methodsmentioning
confidence: 99%
“…Aging alters the morphology of the knee joint (Figure 6A–D ). From the age of three to 17 years the NWI grows smaller, from 0.326 in the youngest to 0.25 in the eldest (Anderson et al, 2001 ; Domzalski et al, 2015 ; Herzog et al, 1994 ; Lima et al, 2020 ; Pekala et al, 2019 ). Everhart et al ( 2014 ) also described a positive age‐related change in the size of the anteromedial ridge at the osteochondral border of the notch.…”
Section: Physiological and Pathological Variability Of The Inmentioning
confidence: 99%
“…Previous studies reported several morphological risk factors for primary ACL ruptures in children and adolescents [6–8, 22, 32]. Risk factors in children include an increased medial and lateral tibial slope, narrower notch width, increased size of tibial eminence and patella alta [6–8, 22, 32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported several morphological risk factors for primary ACL ruptures in children and adolescents [6–8, 22, 32]. Risk factors in children include an increased medial and lateral tibial slope, narrower notch width, increased size of tibial eminence and patella alta [6–8, 22, 32]. The tibial slope has been studied previously as a morphological risk factor for re‐ruptures or revisions in children and adolescents [5, 12, 26].…”
Section: Introductionmentioning
confidence: 99%